PENGARUH MODEL PEMBELAJARAN SAVI TERHADAP KEMAMPUAN BERPIKIR KREATIF BAHASA INDONESIA SISWA KELAS V SD INPRES 3/77 PANYULA KABUPATEN BONE - Rukayah; Firdaus; Andi Asmia sary (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is a quantitative pre-experimental study that aims to determine the effect of the SAVI Learning Model on Students Creative Thinking Skills Indonesian before and after being given treatment. The research design used is a one group pretest-posttest design. The population in this study were all fifth grade students of SD Inpres 3/77 Panyula, Bone Regency with a sample of 21 students selected using saturated sampling techniques. The data collection technique used a written test to measure creative thinking skills. The data analysis technique used is descriptive and inferential statistical analysis. Based on the results of the descriptive analysis, it was obtained that the average pretest score for students' creative thinking abilities was 55.52, which was in the fairly creative category, while the average posttest score after being given treatment was 80.52,which was in the very creative category. The data analysis technique uses descriptive and inferential statistical analysis through the Wilcoxon Signed Rank Test. This shows that there is a significant difference in the creative thinking ability of Indonesian language students of SD Inpres 3/77 Panyula, Bone Regency before and after the implementation of the SAVI learning model. Thus, it can be concluded that the SAVI learning model has a significant effect on the creative thinking ability of Indonesian language students of grade V SD Inpres 3/77 Panyula, Bone Regency.